Penerapan Model Scrum dalam Perancangan Sistem Informasi Penelitian dan Pengabdian Kepada Masyarakat - Edi Kurniawan; Khairul Imtihan; Ahmad Tantoni (LPPM STMIK Royal Kisaran, 2021)
Abstract:Application of the Scrum model in the design of research and community service information systems (Case study at STMIK Lombok), the Institute for Research and Community Service (LPPM) is an activity unit that functions to manage all research and community service activities carried out by lecturers in connection with the lecturer improving the quality of the lecturer. The formulation of the problem is how to design and build a research and community service information system so as to facilitate the process of submitting proposals, accepting, selecting, reviewing, approving, controlling implementation and facilitating reporting. This study uses data collection methods namely observation and interviews, while the system development method uses the Scrum method, the following is a description of the stages of software development using the Scrum method, namely: Produck Backlog, Sprint Backlog, Sprint and Working Increment of the Software. Based on the data analysis, it was concluded that the research and community service information system was designed to facilitate the submission of research proposals as well as the dedication and reporting of research and service activities being carried out by lecturers. Presentation of information in this system includes lecturer data input, input of research proposal, dedication proposal input, print decision letter and report data input. Keywords:Information Systems Research and Community Service, SCRUM Method Abstrak:Penerapan model Scrum dalam perancangan sistem informasi penelititan dan pengabdian kepada masyarakat (Studi kasus di STMIK Lombok), Lembaga Penelititan dan Pengabdian pada Masyarakat (LPPM) adalah sebuah unit kegiatan yang berfungsi mengelola semua kegiatan penelititan dan pengabdian kepada masyarakat yang dilakasanakan oleh dosen dalam kaitan dengan peningkatan kualitas dosen tersebut. Adapun perumusan masalahnya bagaimana merancang dan membangun sistem informasi penelitian dan pengabdian kepada masyarakat sehingga mempermudah dalam proses pengajuan proposal, penerimaan, seleksi, review, persetujuan, pengontrolan pelaksanaan dan mempermudah pelaporan. metode pengembangan sistemnnya menggunakan metode Scrum, uraian dari tahap-tahap pengembangan perangkat lunak menggunakan metode Scrum yaitu : Produck Backlog, Sprint Backlog, Sprint dan Working Increment Of The Software. Berdasarkan analisa data yang dilakukan diperoleh kesimpulan bahwa Sistem informasi penelitian dan pengabdian kepada masyarakat ini dirancang untuk melakukan kemudahan dalam pengajuan usulan proposal penelitian maupun pengabdian dan pelaporan kegiatan penelitian dan pengabdian yang sedang dilakukan oleh dosen. Penyajian informasi dalam sistem ini meliputi input data dosen, input proposal penelitian, input proposal pengabdian, mencetak surat keputusan dan input data laporan. Kata kunci:Sistem Informasi Penelitian dan Pengabdian kepada Masyarakat, Metode SCRUM.